Web services security-don't forget security on the way out security requirements for a web service that are often overlooked. - Luu, Tieu
Typically when we think about security for a Web service, our focus is on how to protect it from unauthorized and malicious users. Thus, we tend to concentrate on such things as authentication of the requestor, checking to see that the requestor is authorized to access the service, validation of the request message and so forth-all things that happen on the way in or during a request for the service. However, there is an equally important set of security functions that need to occur on the way out or after the service has finished processing the request.